Water resources, water productivity, and poverty in the Indus-Ganges River Basin - Sharma, Bharat R.; Amarasinghe, Upali A.; Xueliang Cai; Scott, Christopher A. (2013)
The Indus and Ganges river basins (collectively called the Indus-Ganges Basin) in South Asia covers 2.20 million km2 and is inhabited by a population of more than a billion people, many living in poverty with livelihoods based on waterdependent agriculture. The northwestern Indus basin is highly developed and over-abstracted with only about 10 % net river discharge; whereas in the eastern Ganges basin 37 % of the total precipitation discharges into the Bay of Bengal. The upper reaches of the basin are in the high Himalayas and seriously influenced by the melting of snow and glaciers and impending climate change. The average land and water productivity for the predominant rice-wheat cropping system is low with only about 5 per cent of the basin in the northwest (a regional “bright-spot”) having high productivity that is central to South Asia’s food security. This region is, however, now at risk of groundwater over-exploitation, aggravated mainly by energy and food policies. Access to water resources is relatively low in large areas and critical irrigation water requirements remain unmet due to inadequate access to the resource, high energy prices for water pumping, transboundary nature of the basin, and lack of an organized basin development plan. There is a strong linkage between poverty and low water productivity. Reduction of pervasive rural poverty in the basin can be accelerated by providing access to water to help achieve improvement in productivity, diversification and other pro-poor livelihoods. Based on the hydrological, agricultural and socio-economic variations in the two basins, as summarized in this chapter, the development frameworks and policies need to be regionally differentiated. Pathways to alleviate poverty might include improving agricultural productivity through optimal use of the available water resources, out-scaling bright-spot management practices to other parts of the basin, improved access to groundwater through affordable energy and cooperative tubewells for the smallholders, and policy and investment tools leading to land consolidation, rural infrastructure improvement, and market development.